Clinical features of vitamin D deficiency in children: A retrospective analysis. Issue 196 (February 2020) - Zhang, Xiangmin; Liu, Zongyuan; Xia, Lei; Gao, Junjun; Xu, Falin; Chen, Hao; Du, Yanhua; Wang, Weiwei
Highlights: Vitamin D deficiency occurs not only in children but also in adolescents. Clinical features of vitamin D deficiency are diverse. Clinical symptoms reduced or resolved after vitamin D therapy. Pediatricians should improve their ability to identify different clinical features of vitamin D deficiency. Abstract: Vitamin D is very important for children's health. Previous studies have shown that vitamin D deficiency leads to a series of diseases in adults. However, pediatricians are mostly aware of rickets caused by vitamin D deficiency in children and poorly aware of other symptoms. This study aimed to retrospectively analyze the different clinical features of vitamin D deficiency to enhance identification by pediatricians, thus minimizing misdiagnosis. In this study, we retrospectively analyzed the clinical features of vitamin D deficiency in 268 children aged 0–14 years from June 2016 to May 2018 in the Third Affiliated Hospital of Zhengzhou University. Serum 25-hydroxy vitamin D [25(OH)D] levels were determined using the chemiluminescence method. Of the 268 cases, 101 cases showed movement disorder (37.7%) and 167 nervous system abnormalities (62.3%). Among all cases, 6 were misdiagnosed as febrile seizures (2.23%), 5 as epilepsy (1.86%), 2 as Tourette syndrome (0.74%), and 2 as developmental retardation (0.74%). There were significant differences in patients with clinical characteristics of movement disorder and nervous system abnormalities partly between Pre-and post-vitamin D treatment. This analysis revealed that vitamin D deficiency occurs not only in children but also in adolescents, with diverse clinical features. Therefore, pediatricians should pay more attention to clinical different signs and symptoms, and future studies should be conducted to confirm the mechanisms of these processes.